Convergence in Institutions and Market Outcomes : Cross-country and Time-series Evidence from the Business Environment and Enterprise Performance Surveys in Transition Economies - Mitra, Pradeep; Muravyev, Alexander; Schaffer, Mark E. (2012)
This paper uses firm-level data from the Business Environment and Enterprise Performance Surveys to study the process of convergence of transition countries with developed market economies. The study focuses on competition and market structure, finance and the structure of lending to firms, and how firms respond to the economic environment by restructuring. The authors find substantial evidence of convergence in a number of dimensions. The pattern of growth at the country, sector, and firm levels shows rapid growth of the new private sector and of the micro and small-firm sectors, with the size distribution of firms moving toward the pattern observed in the surveys of developed market economies. In finance, increasing reliance on retained earnings in transition countries reflects a maturation of the sector as new firms come to rely less on informal and family sources of finance. The authors find evidence of an inverse-U pattern, with the peak of restructuring activity taking place in 2002, the middle of the period analyzed. Throughout, the regional patterns suggest greater convergence in the transition countries that joined the European Union in 2004 than in the other, lower-income transition economies.